2020
DOI: 10.1074/jbc.ra120.014122
|View full text |Cite
|
Sign up to set email alerts
|

Acyltransferase-mediated selection of the length of the fatty acyl chain and of the acylation site governs activation of bacterial RTX toxins

Abstract: In a wide range of organisms, from bacteria to humans, numerous proteins have to be posttranslationally acylated to become biologically active. Bacterial repeats in toxin (RTX) cytolysins form a prominent group of proteins that are synthesized as inactive protoxins and undergo posttranslational acylation on ε-amino groups of two internal conserved lysine residues by co-expressed toxin-activating acyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…RtxA belongs to the RTX (Repeats in ToXin) family of pore-forming cytotoxins that are produced by many Gram-negative bacterial pathogens, including the genera Actinobacillus, Aggregatibacter, Bordetella, Escherichia, Mannheimia, Moraxella, Morganella, Pasteurella, Proteus, and Vibrio [12]. Sequence homology with the RTX toxins revealed four functional segments in the 956 residues-long RtxA: (i) a pore-forming domain encompassing residues~140 to 410, harboring four putative transmembrane α-helices; (ii) an acylated segment, where the RtxA protoxin (proRtxA) is posttranslationally activated; recently, we experimentally demonstrated that the acyltransferase RtxC activates proRtxA by fatty acyl modification on lysine residues 558 and 689, primarily with myristoyl and hydroxymyristoyl chains [9,13]; (iii) a typical calcium-binding RTX domain between residues~730 to 810, harboring the conserved repetitions of a nonapeptide motif X-(L/I/F)-X-G-G-X-G-(N/D)-D (where X is any amino acid residue), which form calcium-binding sites and (iv) a C-terminal secretion signal. Upon binding to target cells that is facilitated by membrane cholesterol, RtxA inserts itself into the cell membrane and forms cation-selective membrane pores, which induce cation flux leading to cell death [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…RtxA belongs to the RTX (Repeats in ToXin) family of pore-forming cytotoxins that are produced by many Gram-negative bacterial pathogens, including the genera Actinobacillus, Aggregatibacter, Bordetella, Escherichia, Mannheimia, Moraxella, Morganella, Pasteurella, Proteus, and Vibrio [12]. Sequence homology with the RTX toxins revealed four functional segments in the 956 residues-long RtxA: (i) a pore-forming domain encompassing residues~140 to 410, harboring four putative transmembrane α-helices; (ii) an acylated segment, where the RtxA protoxin (proRtxA) is posttranslationally activated; recently, we experimentally demonstrated that the acyltransferase RtxC activates proRtxA by fatty acyl modification on lysine residues 558 and 689, primarily with myristoyl and hydroxymyristoyl chains [9,13]; (iii) a typical calcium-binding RTX domain between residues~730 to 810, harboring the conserved repetitions of a nonapeptide motif X-(L/I/F)-X-G-G-X-G-(N/D)-D (where X is any amino acid residue), which form calcium-binding sites and (iv) a C-terminal secretion signal. Upon binding to target cells that is facilitated by membrane cholesterol, RtxA inserts itself into the cell membrane and forms cation-selective membrane pores, which induce cation flux leading to cell death [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…The acylation status of the proteins was then characterized by mass spectrometry, which revealed that both Lys860 and Lys983 residues of RTX770 and the Lys983 of the RTX908 were predominantly modified by a mixture of palmitoyl (C16:0) and palmitoleyl (C16:1) chains, with a small proportion of myristoyl (C14:0) and octadecenoyl (C18:1) groups (data not shown). Hence, the overall acylation status of the acylated proteins resembled that of intact recombinant CyaA ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The acylation status of the proteins was determined as described previously ( 6 ). Briefly, the proteins were digested in 25 mM ammonium bicarbonate (pH 8.2) and 4 M urea at a trypsin/protein ratio of 1:50 for 6 h at 30 °C followed by addition of the second portion of trypsin to a final ratio of 1:25 and incubation for another 6 h at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the proper cofactors and buffer conditions are determined for an enzyme of interest, measuring its activity in regulating KFA can be straightforward. Assays for RtxC enzymes indirectly measure activity by taking advantage of the hemolytic action of their cognate RtxA proteins (Bellalou et al, 1990;Linhartova et al, 2010;Osickova et al, 2020). This is not a broadly applicable technique for KFA enzymes and as such will not be further elaborated on.…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%